Utilization of PDAM Sedimentation Sludge as a Multi Soil Layering (MSL) Substance in the Degradation of Liquid Waste Contaminants from the Tofu Industry - Mullah, Ama; Aida, Nur; Syakira, Aisya; Hamdan, Abd Mujahid (Phi: Jurnal Pendidikan Fisika dan Terapan, 2024)
Multi Soil Layering (MSL) is a procedure for treating liquid waste that employs soil as its primary medium. In addition to soil as the primary medium, it can also use sedimentation waste (PDAM) as an alternative. This study included two variations: HLR value variations and HRT value variations. The results indicated that the HLR values were 11.48 L/m2/hour, 4.76 L/m2/hour, and 2.48 L/m2/hour, with 2.48 L/m2/hour exhibiting the highest level of effectiveness. The pH and DO values changed to 7.4 and 19.5 mg/L, respectively, and the TSS value effectiveness reached 76.32%, the TDS value degradation reached 75.21%, the turbidity degradation reached 99.69%, and the COD degradation reached 99.66. At the HRT values of 4 hours, 6 hours, 8 hours, 10 hours, and 12 hours, the effectiveness level of the greatest HRT variation occurred at 12 hours, where the value of changes in pH and DO became 19.5 mg/L and became 7.5, and the effectiveness COD value degradation reached 98.95%, BOD value degradation reached 51.11%, and TSS degradation reached 73.5%. The obtained results indicate that the MSL method with PDAM sedimentation waste material is capable of reducing pollutant levels in the tofu manufacturing industry.